The functions of sterling - Meyer, Frederick Victor (London : Croom Helm Ltd, 1973)
The book discusses the vital questions why sterling is under pressure?. It also examines critically the internal and external performance of sterling throughout the twentieth century.
Includes bibliographical references and index.
usc 28/06/2017
Loans
Keywords: Currency question; Monetary policy; Great Britain